Evaluating e-Connect: Mitigating Race by Gender Disparities in Behavioral Health Referral Among Youths on Probation, Northeast United States, 2019. - Ryan, Margaret E.; Elkington, Katherine S.; Sarapas, Casey; Sichel, Corianna; Taxman, Faye; Dennis, Michael L.; Wasserman, Gail A. (American Journal of Public Health, 2023)
Addressing the behavioral health needs of youths involved in the justice system is key to reducing recidivism risk and preventing long-term system involvement. However, rates of treatment referral and initiation remain low, especially among minoritized youths and boys. The e-Connect System, a digital, clinical decision support system, addresses this problem by increasing rates of behavioral health treatment referral and initiation rates among youths on probation. In this study, we examine whether e-Connect helps improve equity in referral and treatment initiation outcomes. (Am J Public Health. 2023;113(12):1267–1270. https://doi.org/10.2105/AJPH.2023.307417)